2009
DOI: 10.1017/s0022215109004861
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of haemangiomas in the sinonasal cavity

Abstract: Although past studies have described external approach sinonasal surgery as the mainstay of treatment, our results imply that endoscopic excision of sinonasal haemangiomas yields excellent outcomes in terms of tumour control and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 19 publications
2
61
0
1
Order By: Relevance
“…1 Without knowledge of the typical clinical presentation and the complete study of imaging findings, the entity tends to be clinically and radiologically confused with neoplastic processes and even malignancy. 2 This entity has been described in the literature in different terms, including cavernous hemangioma, [3][4][5][6][7] organized or organizing hematoma, [8][9][10][11] hematoma-like mass of the maxillary sinus, 12 and SAP. 1,2,13,14 This lesion is difficult to remove en bloc and is easily broken during excision, so the sampling inconsistencies related to lesional fragility are likely responsible for the wide variation in pathologic description and terminology.…”
mentioning
confidence: 99%
“…1 Without knowledge of the typical clinical presentation and the complete study of imaging findings, the entity tends to be clinically and radiologically confused with neoplastic processes and even malignancy. 2 This entity has been described in the literature in different terms, including cavernous hemangioma, [3][4][5][6][7] organized or organizing hematoma, [8][9][10][11] hematoma-like mass of the maxillary sinus, 12 and SAP. 1,2,13,14 This lesion is difficult to remove en bloc and is easily broken during excision, so the sampling inconsistencies related to lesional fragility are likely responsible for the wide variation in pathologic description and terminology.…”
mentioning
confidence: 99%
“…However, minimally invasive endoscopic approaches are more comfortable for the patients especially at advanced ages and having accompanying systemic diseases. Song et al (11) reviewed 22 patients who had undergone endoscopic excision of sinonasal cavity hemangioma and they reported that endoscopic excision of sinonasal hemangioma yields excellent outcomes in terms of tumor control and safety. We also preferred endoscopic excision in our case, since he was elderly and had accompanying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative transarterial embolization can decrease the tumor size and reduce the risk of hemorrhage during surgery. [9][10][11][12]…”
Section: Discussionmentioning
confidence: 99%